Dinamika Proses pada Sistem Pemanas Tangki Berpengaduk dengan Arus Bypass - Yulius Deddy Hermawan (Seminar Nasional Teknik Kimia Kejuangan, 2014)
The liquid concentration and temperature dynamic behavior of a stirred tank heater with bypass stream (STHB) has been studied experimentally. A cylinder tank was designed and arranged for experimentation in laboratory. The tank has two input streams, stream-1 (salt solution with its volumetric rate of f1 [cm3/sec], salt concentration of cg1 [gr/cm3]) and stream-2 (water-stream with its volumetric rate of f2 [cm3/sec]). A part of the stream-1 was bypassed (f3 [cm3/sec]) and mixed with the output stream of the tank (f5 [cm3/sec]). The electric heater was employed for heating liquid in the tank. Since the tank was designed overflow, the liquid volume in tank was always constant. In this work, the mass and thermal disturbance load has been made based on step increase and decrease. Those disturbance included the changes of the bypass volumetric rate (f3), the water volumetric rate (f2), and the electric heat (qe). The dynamic behavior of the STHB has also been explored. As can be seen from our investigation in laboratory, the STHB produced a stable response. Furthermore, the open loop dynamic simulation using computer programing was also done, and its simulation results were compared with the experiment data from laboratory. The developed mathematical model of the STHB has been solved numerically. Scilab software was chosen to examine such mathematical model. This study also revealed that the trends of simulation results were quite similar with those in our experiment results.